2015
DOI: 10.1007/s40553-015-0059-4
|View full text |Cite
|
Sign up to set email alerts
|

Fuel-Cladding Interaction Between U-Pu-Zr Fuel and Fe

Abstract: This work investigates fuel-cladding chemical interaction (FCCI) between U-25Pu-14Zr (in wt pct) fuel and pure Fe at elevated temperatures, understanding of which is critical for evaluation of the fuel performance. Phases and microstructure formed in the quaternary uranium-plutonium-zirconium-iron (U-Pu-Zr-Fe) system were characterized using the transmission electron microscopy technique. Phases formed within the FCCI layer were identified using selective area electron diffraction (SAED) analysis as Fe 2 U (Fd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…showed that even though chemical compositions of high-Zr inclusions are consistent with previous reports, the crystal structure of precipitates is face-centered cubic [16]. Previous work on U-25Pu-14Zr (wt%) fuel showed formation of β-Zr precipitates as well [18]. Formation of fcc Zr inclusion has been reported in nanocrystals and thin films but not in larger crystals [19][20].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…showed that even though chemical compositions of high-Zr inclusions are consistent with previous reports, the crystal structure of precipitates is face-centered cubic [16]. Previous work on U-25Pu-14Zr (wt%) fuel showed formation of β-Zr precipitates as well [18]. Formation of fcc Zr inclusion has been reported in nanocrystals and thin films but not in larger crystals [19][20].…”
Section: Resultssupporting
confidence: 83%
“…Figure 10 shows bright-field transmission electron micrograph of the Zr precipitate observed in the third lift-out and its corresponding experimental and simulated electron diffraction patterns. Formation of high-Zr inclusions has been previously reported in a variety of transmutation fuels [11][12][13][14][15][16][17][18]. These precipitates were assumed to be α-Zr stabilized by dissolved impurities such as N, O, C, Cl, C, and Si.…”
Section: Resultsmentioning
confidence: 99%
“…As the fuel swells during burnup, the lanthanide (Ln) fission products with particularly abundant cumulative yield can migrate to the fuel periphery and form low-melting point intermetallic compounds with cladding constituents such as Fe and Ni [2]. This chemical interaction between the fission products and the cladding can not only reduce cladding thickness, but also degrade its load-bearing capability [3]. The FCCI phenomenon is deemed as one of the limiting factors of operation of this particular fuel.…”
Section: Introductionmentioning
confidence: 99%